Palmitoylethanolamide, a Natural Retinoprotectant: Its Putative Relevance for the Treatment of Glaucoma and Diabetic Retinopathy - Jan M. Keppel Hesselink; Ciro Costagliola; Josiane Fakhry; David J. Kopsky (Journal of Ophthalmology)
Retinopathy is a threat to the eyesight, and glaucoma and diabetes are the main causes for the damage of retinal cells. Recent insights pointed out a common pathogenetic pathway for both disorders, based on chronic inflammation. Palmitoylethanolamide (PEA) is an endogenous cell protective lipid. Since its discovery in 1957 as a biologically active component in foods and in many living organisms, around 500 scientific papers have been published on PEA’s anti-inflammatory and neuron-protective properties. PEA has been evaluated for glaucoma, diabetic retinopathy, and uveitis, pathological states based on chronic inflammation, respiratory disorders, and various pain syndromes in a number of clinical trials since the 70s of 20th century. PEA is available as a food supplement (PeaPure) and as diet food for medical purposes in Italy (Normast, PeaVera, and Visimast). These products are notified in Italy for the nutritional support in glaucoma and neuroinflammation. PEA has been tested in at least 9 double blind placebo controlled studies, among which two studies were in glaucoma, and found to be safe and effective up to 1.8 g/day, with excellent tolerability. PEA therefore holds a promise in the treatment of a number of retinopathies. We discuss PEA as a putative anti-inflammatory and retinoprotectant compound in the treatment of retinopathies, especially related to glaucoma and diabetes.